The Competencies of Human Talent Linked to the Development of Community Based Rural Tourism in the Province of Chimborazo Ecuador - CEJAS MARTÍNEZ, Magda Francisca; ALDAZ HERNÁNDEZ, Silvia Marieta; QUEVEDO BÁEZ, Luis Alberto; QUIÑÓNEZ BEDÓN, Mayra Fernanda; MENDOZA VELAZCO, Derling José (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020DO - 10.14505/jemt.v11.6(46).10, 2020)
Human talent represents today for the rural and community tourism a fundamental axis for the improvements of income and sustainable development for the communities of this sector so absent of the governmental policies. Tourism in general, according to international organizations, is considered a strategic axis for the nations of the world, given its planetary reach in the economic and social sector, but also because of the advances that are generated through it in communities, regions and countries.  The objective of the study is to evaluate the human talent and competencies in tourism that are related to the work of tourism establishments in the provinces of Chimborazo. It also seeks to highlight the key capacities in this sector of the Ecuadorian economy. The methodology of the study responds to the quantitative, documentary method based on interpretation, applying an instrument that resulted in the presentation of the key and identifying competencies of the tourism professional who works in rural and community areas. It is concluded that the Province of Chimborazo is part of the programs of interest for the development of tourism in Ecuador, being necessary to potentiate the competencies that characterize the human talent that works in tourism.